REDUCING POWER ACTIVITY OF MILKFISH (CHANOS CHANOS) BONE HYDROLYSATES PRODUCED BY DIFFERENT RETORTING TIMES - Fahlivi, Muhammad Rizal; Hardoko; Prihanto, Asep Awaludin; Widodo, Maheno Sri (Journal of Environmental Engineering and Sustainable Technology, 2025)
Bioactive peptides recovered from fish-processing by-products have emerged as promising natural antioxidants with potential applications in functional foods and nutraceuticals. In the present study, protein hydrolysates were prepared from milkfish (Chanos chanos) bones by high-temperature retorting at 121°C for 15 and 120 min to evaluate the influence of extraction time on their reducing power. Following retorting, the hydrolysates were centrifuged, neutralized with phosphoric acid, freeze-dried, and characterized for protein content, degree of hydrolysis (DH), molecular weight distribution, and reducing power activity. The freeze-dried hydrolysates contained 85.10–89.27% protein, while DH values ranged from 67.88% to 72.10%. SDS-PAGE analysis revealed that the 15-min hydrolysate mainly consisted of proteins within the molecular weight range of 30,000–70,000 Da, whereas the 120-min treatment predominantly generated peptide fractions below 14,400 Da. Among the retorting conditions evaluated, the hydrolysate produced after 120 min exhibited the highest reducing power (0.61 ± 0.01 at 12 mg/mL). These findings demonstrate that retorting time markedly influences peptide characteristics and antioxidant capacity. Nevertheless, additional studies employing intermediate retorting durations are required to identify the optimum processing conditions for maximizing the reducing power of milkfish bone hydrolysates.